IL-10-Producing CD1dhiCD5+ Regulatory B Cells May Play a Critical Role in Modulating Immune Homeostasis in Silicosis Patients - Chen, Ying; Li, Chao; Lu, Yiping; Zhuang, Huiying; Gu, Weijia; Liu, Bo; Liu, Fangwei; Sun, Jinkai; Yan, Bo; Weng, Dong; Chen, Jie (Frontiers in Immunology, 2017)
Silicosis is characterized by chronic lung inflammation and fibrosis, which are extremely harmful to human health. The pathogenesis of silicosis involves uncontrolled immune processes. Evidence supports that regulatory B cells (Bregs) produce negative regulatory cytokines, such as IL-10, which can negatively regulate immune responses in inflammation and autoimmune diseases. Our previous study found that IL-10-producing B cells (B10) were involved in the development of silica-induced lung inflammation and fibrosis of mice. However, little is known about the role of regulatory B cells in silicosis patients. In this study, we found that serum concentrations of IL-10 were significantly increased in silicosis patients by using protein array screening.We further determined that the frequency of IL-10-producing CD1dhiCD5+regulatory B cells, not IL-10-producing non-B lymphocytes, was significantly higher in silicosis patients compared to subjects under surveillance and healthy workers by flow cytometry. We also found that regulatory T cells (Tregs) and Th2 cytokines (IL-4, IL-5 and IL-13) were significantly increased in silicosis patients. Th1 cytokines (IFN-γ, IL-2 and IL-12) and inflammatory cytokines (IL-1β, IL-6 and TNF-α) were not significantly different between silicosis patients, subjects under surveillance and healthy workers. Our study indicated that IL-10-producing CD1dhiCD5+regulatory B cells might maintain Tregs and regulate Th1/Th2 polarization in silicosis patients, suggesting that IL-10-producing Bregs may play a critical role in modulating immune homeostasis in silicosis patients.